2021
DOI: 10.1088/1748-9326/abd660
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the conceptual frameworks and methods of the food–energy–water nexus at the household level for development-oriented policy support: a systematic review

Abstract: This paper undertakes a systematic review of the literature to understand current trends in the food–energy–water (FEW) nexus for development-oriented policy support. The paper follows three steps: (a) a bibliometric analysis of FEW nexus research, (b) a content analysis of FEW nexus research, and (c) development of a framework that fills existing gaps in FEW nexus research. The review found that FEW nexus approaches have gained ground in academia as a resource management tool and policy guide; however, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 114 publications
2
2
0
Order By: Relevance
“…Unfortunately, distribution in the scale of focus found in Nexus documentation may further reflect a failure to adopt an outcome orientation. Consistent with the previous findings of Itayi et al (2021) who found that Nexus research often focused on large (national, regional and global) scales and Chang et al (2021) who found 34% out of about 100 analysed WEF articles focused on the global scale, our review found Nexus documents were most often focused at larger scales (e.g. global and national).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unfortunately, distribution in the scale of focus found in Nexus documentation may further reflect a failure to adopt an outcome orientation. Consistent with the previous findings of Itayi et al (2021) who found that Nexus research often focused on large (national, regional and global) scales and Chang et al (2021) who found 34% out of about 100 analysed WEF articles focused on the global scale, our review found Nexus documents were most often focused at larger scales (e.g. global and national).…”
Section: Discussionsupporting
confidence: 92%
“…Further, there is fairly diverse sectoral participation in WEF activities. Similar to the results of Itayi et al (2021) who determined water‐centrism of WEF Nexus by analysing frequency of keywords in research papers and determined water as the most common keyword and energy as the least, our paper used a larger and diverse set of documents to confirm that Nexus activities are indeed more often driven by the water sector. Nonetheless, our paper was able to add considerable nuance by identifying that sectoral diversity in project teams is considerable regardless of sectoral driver—with the exception of the energy sector which may be somewhat underrepresented.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ranging from simpler footprinting and material flow models [25,26] to system dynamics [27] and large integrated assessment models (IAM) [28]. Several reviews on FWE modeling show the full scope of approaches [19,[29][30][31]. They have noted that urban FWE models are largely positioned in the realm of industrial ecology, typically applying material flow analyses and similar concepts within urban metabolism frameworks.…”
mentioning
confidence: 99%